2014
DOI: 10.1038/jcbfm.2014.61
|View full text |Cite
|
Sign up to set email alerts
|

Neural Stem Cell Protects Aged Rat Brain from Ischemia–Reperfusion Injury through Neurogenesis and Angiogenesis

Abstract: Neural stem cells (NSCs) show therapeutic potential for ischemia in young-adult animals. However, the effect of aging on NSC therapy is largely unknown. In this work, NSCs were transplanted into aged (24-month-old) and young-adult (3-month-old) rats at 1 day after stroke. Infarct volume and neurobehavioral outcomes were examined. The number of differentiated NSCs was compared in aged and young-adult ischemic rats and angiogenesis and neurogenesis were also determined. We found that aged rats developed larger i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 42 publications
1
77
0
Order By: Relevance
“…First, aged animals after stroke sustain more severe brain injuries compared to young animals [26][27][28], and it's highly probable that different brain damage will induce different angiogenesis. Second, intravascular flow rate is an important mediator for angiogenesis, and previous studies showed that aging is greatly related to blood flow velocity and flow volume [29].…”
Section: Discussionmentioning
confidence: 99%
“…First, aged animals after stroke sustain more severe brain injuries compared to young animals [26][27][28], and it's highly probable that different brain damage will induce different angiogenesis. Second, intravascular flow rate is an important mediator for angiogenesis, and previous studies showed that aging is greatly related to blood flow velocity and flow volume [29].…”
Section: Discussionmentioning
confidence: 99%
“…NSCs had a significantly better effect within the first 2 wk, whereas iPSCs had a more steady effect over 2 wk. This observation was not entirely unexpected as it has been found that iPSCs could form functional neurons and improve the neurologic function up to 4-12 wk (19,27), whereas NSCs have significant therapeutic effects at 2 wk after transplantation (30,31), yet the prolonged effect in vivo has not been universally demonstrated. We suppose that cerebral ischemia appeared to activate the neurogenesis program: transplanted NSCs may act as a functional cell type in an earlier time course after transplantation, whereas iPSCs might differentiate into a more specific functional cell type before promoting the recovery of cerebral ischemia.…”
Section: Discussionmentioning
confidence: 91%
“…Cerebral ischemia reperfusion model (CIRI) is a tissue injury aggravated pathological phenomenon caused by tissue ischemia certain time and followed restore the blood supply [11]. Cerebral ischemia reperfusion injury is conventional case in clinical, the event can cause a large number of neuronal apoptosis, greater harm to the patients [12]. Establishing cerebral ischemia-reperfusion model, in order to simulate the human ischemia-reperfusion injury, to identify the agents can greatly reduce the cerebral ischemia injury, to reduce the suffering of patients and to improve their quality of life [13].…”
Section: Discussionmentioning
confidence: 99%